Manipulation of Polyhydroxybutyrate Properties through Blending with Ethyl-Cellulose for a Composite Biomaterial - Rodman T. H. Chan; Christopher J. Garvey; Helder Marçal; Robert A. Russell; Peter J. Holden; L. John R. Foster (International Journal of Polymer Science)
Polyhydroxybutyrate (PHB) is widely used as a biomaterial in medical and tissue-engineering applications, a relatively high crystallinity limits its application. Blending PHB with ethyl-cellulose (EtC) was readily achieved to reduce PHB crystallinity and promote its degradation under physiological conditions without undue influence on biocompatibility. Material strength of composite films remained unchanged at 6.5 ± 0.6 MPa with 40% (w/w) EtC loadings. Phase separation between the two biopolymers was determined with PHB crystallinity decreasing from 63% to 47% for films with the same loading. This reduction in crystallinity supported an increase in the degradation rates of composite films from 0.39 to 0.81% wk−1 for PHB and its composite, respectively. No significant change in morphology and proliferation of olfactory ensheathing cells were observed with the composites despite significant increases in average surface roughness (Ra) of the films from 2.90 to 3.65 μm for PHB and blends with 80% (w/w) EtC, respectively.